Domain Adaptation and Transfer Learning methods enhance Deep Learning Models used in Inner Speech Based Brain Computer Interfaces - Zablocki, Luciano Ivan (2022)
Brain Computer Interfaces are useful devices that can partially restore the communication from severe compromised patients. Although the advances in deep learning have significantly improved brain pattern recognition, a large amount of data is required for training these deep architectures. In the last years, the inner speech paradigm has drew much attention, as it can potentially allow a natural control of different devices. However, as of the date of this publication, there is only a small amount of data available in this paradigm. In this work we show that it is possible, by means of transfer learning and domain adaptation methods, to make the most of the scarce data, enhancing the training process of a deep learning architecture used in brain computer interfaces.